A Study on Students’ Psychological Problems of Speaking - Prasetyaningrum, Ari; Jaelani, Selamet Riadi; Asrobi, Maman; Isroini, Hulmiya (English Language in Focus (ELIF), 2023)
The most difficult ability to learn is speaking. Thus, it is essential to understand speaking psychological problems during the teaching and learning process. The researchers used a descriptive quantitative method to conduct this present study. The goal of this research was to gain in a deeper understanding about the types and underlying causes of students' psychological speaking problems among eighth-graders of MTs NW Sepit. There were twenty students taken as participants. Data then were collected through questionnaire and interview. The result of this research indicated that the students of MTs. NW Sepit faced the psychological problems in learning speaking. From the data gained in questionnaire and interview, speaking difficulties were most frequently caused by a lack of confidence (50%) followed by a lack of motivation (38, 46%) and nervousness (11, 53%), which was the least common. It was hoped that by putting this study into practice, students would become more fluent in English and experience less psychological speaking problems.